STM study of the (001) and (110) surfaces of magnetite - Ceballos, Sergio F. (Trinity College (Dublin, Ireland). School of Physics, 2005)
In this thesis the surface of single crystals and thin films of magnetite (001) and (110) have been studied by scanning tunneling microscopy (STM), scanning tunneling spectroscopy (STS), Auger electron spectroscopy (AES) and low-energy electron diffraction (LEED). The use of STM tips made of magnetic materials is highlighted in this work. A novel technique has been developed by the author in order to provide STM tips made of paramagnetic, ferromagnetic and antiferromagnetic materials. Special emphasis has been placed on the study and characterization of tips made of antiferromagnetic MnNi alloy. Chemical and magnetic characterization has been performed by AES, X-ray diffraction (XRD), alternating gradient force magnetometer (AGEM) and transmission electron microscope (TEM). Scanning electron microscope (SEM) has also been employed for characterization of the tips. The potential of the MnNi tips for SP-STM measurements has been confirmed by STS/STM studies of Mn/Fe(001), a test sample whose magnetic properties are well known. These tips are routinely used by the group for SP-STM experiments on magnetite.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin